Deterring the Drunk Driver: An Examination of Conditional Deterrence and Self-Reported Drunk Driving - Stringer, Richard J. (Crime & delinquency, 2024)
This project uses a representative U.S. population sample and Generalized Structural Equation Modeling (GSEM) to explore the deterrence of driving under the influence (DUI) and it’s moderation by the differential deterrability of problem and non-problem drinkers. As hypothesized, the results indicate that personal and vicarious experiences with punishment and punishment avoidance were significant predictors of punishment certainty and self-reported DUI. Significant heterogeneity in both the formulation of perceived certainty of punishment and the relationship between this perception and DUI also exists between problem and non-problem drinkers. Most notably, certainty of punishment was a more robust negative predictor of DUI offending for problem drinkers, and prior punishment appears to have little effect on perceptions of punishment certainty for problem drinkers.